Psychometric Properties of Indonesian Version Co-Worker Support Scale - Unika Prihatsanti (Jurnal Psikologi, 2021)
This study aimed to validate the Indonesian Version of the Co-worker Support Scale. A scale used to measure co-support in organization. The International Test Commission (ITC) Guidelines for Translating and Adapting Test Second Edition procedure used to adapt this scale. A total of 318 employees (M = 44%, F = 56%; SD Age = 8.3) from various organizations were involved in this study. Based on the Rasch model analysis, it indicated that the Co-worker Support Scale has good internal consistency. The result showed that the scale’s factor structure was unidimensional, RV= 60.8%. It means that the items can be effectively able to measure co-worker support. The significant chi-square value indicates that the data is fit to the model, χ2 (4118) = 8017.19, p < .01. The answer choice category option with 5 answer choices can be preserved. Moreover, no differential item functioning was found based on gender, education level, and type of organization. Overall, the results indicated that this 14-item scale, including its psychometric properties, was satisfactorily reliable and valid to measure co-worker support in the organizational context in Indonesia.